Cash Reserve, CEO Health Risk, the Price Reaction due to COVID-19 First Announcement on Leisure Industry - Arsyad, Muhammad Afif; Utama, Cynthia Afriani (JDM (Jurnal Dinamika Manajemen), 2022)
This study investigates stock market reaction in leisure industries to the first Government announce- ment of the COVID-19 outbreak in Indonesia on March 2, 2020. This study used event study meth- odology and was supported by multiple linear regression to analyze the relationship between market reaction and independent variables. The analysis was further modeled using Fama French three-fac- tor models to estimate the expected return on firms due to the first COVID-19 outbreak announce- ment. Based on our calculation of Cumulative abnormal returns, the stock of tourism industries has more negative reaction towards a confirmed first case of COVID-19 compared to other industries. We also find that Indonesian firms with greater cash reserves experienced less negative stock returns while firms with higher leverage ratios were penalized more. Additionally, this paper does not find that firms with Chief Executive Officers (CEO) who were exposed to significant health risks from COVID-19 experienced worse stock market performances.